Status of knowledge of project management in geothermal projects in emerging markets - Sunna Björg Reynisdóttir 1985- (2020)
Research has shown that standardized project management processes and sound decision making can increase how successfully projects meet their requirements such as being delivered on time, on budget and of agreed upon quality. This paper looks into the project management process and governance present within organisations involved in the development of geothermal projects in various emerging markets. How formal and standardized are their project processes and what are some of the challenges they face when executing their projects. The research was conducted through interviews with experienced project managers from emerging markets, all working for a public entity and they are all former fellows of the UNU-GTP (now GRÓ-GTP) program in Iceland. The purpose was to gain insight from their experience in developing and executing challenging projects in emerging geothermal markets.